Identification of bolting-related microRNAs and their targets reveals complex miRNA-mediated flowering-time regulatory networks in radish (Raphanus sativus L.) - Nie, Shanshan (Sci Rep, 2015)
MicroRNAs (miRNAs) play vital regulatory roles in plant growth and development. The phase transition from vegetative growth to flowering is crucial in the life cycle of plants. To date, miRNA-mediated flowering regulatory networks remain largely unexplored in radish. In this study, two small RNA libraries from radish leaves at vegetative and reproductive stages were constructed and sequenced by Solexa sequencing. A total of 94 known miRNAs representing 21 conserved and 13 non-conserved miRNA families, and 44 potential novel miRNAs, were identified from the two libraries. In addition, 42 known and 17 novel miRNAs were significantly differentially expressed and identified as bolting-related miRNAs. RT-qPCR analysis revealed that some miRNAs exhibited tissue- or developmental stage-specific expression patterns. Moreover, 154 target transcripts were identified for 50 bolting-related miRNAs, which were predominately involved in plant development, signal transduction and transcriptional regulation. Based on the characterization of bolting-related miRNAs and their target genes, a putative schematic model of miRNA-mediated bolting and flowering regulatory network was proposed. These results could provide insights into bolting and flowering regulatory networks in radish, and facilitate dissecting the molecular mechanisms underlying bolting and flowering time regulation in vegetable crops.